ADDIE Model in Developing Culture-Based Learning Modules - Riska Dia Sapitri; Satutik Rahayu; I Putu Artayasa; Ryya Aulia Assiri (Indonesian Journal of Innovation in Education Research, 2026)
The development of culture-based learning modules is increasingly important in creating contextual, meaningful, and relevant learning for students. This study aims to analyze the use of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model in the development of culture-based modules and assess its impact on the quality of the process and learning outcomes. The method employed is a qualitative descriptive approach, based on a literature review of 24 relevant scientific articles. Data were analyzed using content analysis techniques, mapping the application of the ADDIE model at each stage, and identifying patterns of integration of local wisdom in the modules. The results indicate that cultural integration is consistently carried out across all ADDIE stages. The analysis stage focuses on mapping students' needs and the relevance of local culture; the design stage incorporates cultural elements in the structure, illustrations, and learning activities; the development stage produces authentic and engaging digital and printed modules; the implementation stage shows increased motivation and learning participation; and the evaluation stage demonstrates the effectiveness of the modules by improving learning outcomes, cultural literacy, and character building. All studies show a high level of module validity and positive responses from students and teachers. Overall, the application of the ADDIE model has proven efficient and flexible in the development of culture-based learning modules. Cultural integration not only strengthens conceptual understanding, but also fosters students' appreciation for local identity